2023
DOI: 10.1111/dgd.12839
|View full text |Cite
|
Sign up to set email alerts
|

The dopamine effect on sea urchin larvae depends on their age

Abstract: Activation of the dopamine type-D 2 receptor in late gastrula of sea urchins is known to decrease the growth rate of post-oral arms of larvae, and, as a result, the phenotype of these larvae mimics that of larvae developing in the abundance of food. Our data indicate that the effect of dopamine on sea urchin larvae is stage-dependent. In our experiment, the early four-armed plutei (96 hours post fertilization, hpf) of Stron-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…A correlation is observed, wherein heightened DA levels correspond to diminished arm length. Concurrently, it has been observed that the responsiveness to DA undergoes modifications This is a provisional file, not the final typeset article with larval maturation (Kalachev and Tankovich, 2023). Noteworthy is the existence of analogous data for M. nudus, a species explored in this study (Kalachev, 2020).…”
Section: Post-oral Dopaminergic Neurons Heterochrony and Dopamine-med...mentioning
confidence: 79%
“…A correlation is observed, wherein heightened DA levels correspond to diminished arm length. Concurrently, it has been observed that the responsiveness to DA undergoes modifications This is a provisional file, not the final typeset article with larval maturation (Kalachev and Tankovich, 2023). Noteworthy is the existence of analogous data for M. nudus, a species explored in this study (Kalachev, 2020).…”
Section: Post-oral Dopaminergic Neurons Heterochrony and Dopamine-med...mentioning
confidence: 79%
“…A correlation is observed, wherein heightened DA levels correspond to diminished arm length. Concurrently, it has been observed that the responsiveness to DA undergoes modifications with larval maturation ( Kalachev and Tankovich, 2023 ). Noteworthy is the existence of analogous data for M. nudus , a species explored in this study ( Kalachev, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…Many bioamine neurotransmitters, such as 5-HT, dopamine, adrenaline, and noradrenaline, have been identified in different tissues of echinoderms using biochemical and histochemical methods [21,44,109,110]. These neurotransmitters are involved in regulating a variety of physiological behaviors in echinoderms, including reproduction, ovarian maturation, embryonic development, morphogenesis, settlement, and swimming behavior [21,93,[110][111][112][113]. At the same time, the effects of numerous bioamines on various echinoderm muscles have been examined, and their functional characteristics are highly variable [21,86].…”
Section: Bioamine Neurotransmittersmentioning
confidence: 99%